Patients' experiences of breathing retraining for asthma: a qualitative process analysis of participants in the intervention arms of the BREATHE trial. (December 2017) - Arden-Close, Emily; Yardley, Lucy; Kirby, Sarah; Thomas, Mike; Bruton, Anne
Abstract Poor symptom control and impaired quality of life are common in adults with asthma, and breathing retraining exercises may be an effective method of self-management. This study aimed to explore the experiences of participants in the intervention arms of the BREATHE trial, which investigated the effectiveness of breathing retraining as a mode of asthma management. Sixteen people with asthma (11 women, 8 per group) who had taken part in the intervention arms of the BREATHE trial (breathing retraining delivered by digital versatile disc (DVD) or face-to-face sessions with a respiratory physiotherapist) took part in semi-structured telephone interviews about their experiences. Interviews were analysed using thematic analysis. Breathing retraining was perceived positively as a method of asthma management. Motivations for taking part included being asked, to enhance progress in research, to feel better/reduce symptoms, and to reduce medication. Participants were positive about the physiotherapist, liked having the materials tailored, found meetings motivational, and liked the DVD and booklet. The impact of breathing retraining following regular practice included increased awareness of breathing and development of new habits. Benefits of breathing retraining included increased control over breathing, reduced need for medication, feeling more relaxed, and improved health and quality of life. Problems included finding time to practice the exercises, and difficulty mastering techniques. Breathing retraining was acceptable and valued by almost all participants, and many reported improved wellbeing. Face to face physiotherapy was well received. However, some participants in the DVD group mentioned being unable to master techniques. Asthma: Patients receptive to breathing retraining Patients with asthma taught how to change their unconscious breathing patterns generally like non-pharmacological interventions. Researchers in the UK, led by Mike Thomas from the University of Southampton, interviewed 16 people about their experiences in a trial that tested breathing retraining exercises delivered by DVD or face-to-face sessions with a respiratory physiotherapist. Overwhelmingly, trial participants reported that breathing retraining sessions gave them greater control over their symptoms, helped them relax, improved their quality of life and reduced the need for medications. Some participants who received DVD instruction said they had trouble mastering the techniques, and many in both groups found it hard to find time to practice the exercises. Overall, however, patients were positive about the experience. The authors conclude that breathing exercises are likely to be a well-received method of asthma management.